Exploring the therapeutic potential of Eleusine indica plant: promising antioxidant and analgesic activity with lack of antimicrobial and thrombolytic activity - Jahan, Farhana Israt; Anik, Asif Hossain; Sumaiya Akter (Journal of Applied Pharmaceutical Research, 2025)
Background: Eleusine indica is used as a traditional medicine in Bangladesh. It is significantly valued for its wound-healing properties and is often used as an anthelmintic and pain reliever in rural areas. Objective: This study examines the pharmacological effects of Eleusine indica methanolic extracts, highlighting antioxidant, antimicrobial, thrombolytic, and analgesic properties in animal models. Also, contribute to future research directions. Methods: The antioxidant properties were determined using the DPPH free radical scavenging assay, with ascorbic acid as the positive control, and the inhibition percentage was calculated. Antimicrobial activity was determined using the disc diffusion method. The thrombolytic Potential was determined through in vitro clot lysis assays. However, the % of clot lysis was used to gauge the thrombolytic effects. For assessing analgesic activity, Swiss albino mice were utilized; analgesic efficacy was evaluated by calculating the percentage inhibition against abdominal writhing. Results: The free radical scavenging assay demonstrated with an IC50 of 43.67 μg/ml, comparable to ascorbic acid's IC50 of 36.22 μg/ml. However, the methanolic extract showed no antimicrobial activity. In thrombolytic assays, the extract induced 26.79% clot lysis. With a 55.57% reduction in writhing, the extract group (500 mg/kg) exhibited significant analgesic activity, approaching the standard group's 73% inhibition. Conclusion: The Outcome of the study shows Eleusine indica has potential antioxidant and analgesic activity, with a lack of antimicrobial and thrombolytic properties. The results support the application of traditional medicine. highlighting the importance of antioxidant and analgesic activity, in future investigations aimed at isolating and identifying the specific compounds driving its pharmacological activities.